Sustainable agriculture : technology, planning and management - Salazar, Augusto; Rios, Ismael (Agriculture issues and policies series., 2010)
"Sustainability is defined as the use of natural resources without risking their exploitation by future generations. Agriculture can only be considered as sustainable if it includes a suitable system of plant genetic resources conservation. In this book, the modern concepts of agricultural sustainability and the economics of agricultural sustainability are discussed. A new framework for analysis and improvement of the governance of agrarian sustainability is presented. In addition, specific modes for environmental governance in Bulgarian agriculture are identified and the efficiency of market, private and public modes are assessed. Furthermore, the regulation measures through nutrient solution regulation and environmental control on nitrate accumulation in vegetables are summarized, highlighting the control strategy. Arguments for and against government strategies to promote large-scale agricultural units in emerging economies are also analyzed and an economic theory that models agricultural supply in emerging economies is presented. Other chapters in this book describe the role of fluorescent pseudomonads in soil fertility, biodegradation of agricultural pollutants, plant growth-promotion, biocontrol of weeds, phytopathogens and nematodes. Information about the global relevance of China's and Australia's cotton industries are also given, and the structure and other significant features of their cotton industries are compared. The main characteristics and importance of plant growth-promoting bacteria in sustainable agriculture in tropical agriculture are looked at as well. Developing alternative ways to control plant disease, with good agronomic and horticultural practices is becoming the focus of many researchers. This book also includes information on ways to control plant diseases in order to maintain the quality and abundance of food produced by growers around the world."--Publisher's description.